Kepemimpinan Kepala Sekolah dalam Manajemen Kelas Sekolah Dasar - Sri Marmoah; Beta Nanda Mulia; Ainun Nafisah (Universitas Batanghari Jambi, 2023)
: The principal is in charge of guiding the school and must possess strong visionary, managerial, and leadership qualities. The purpose of this study is to ascertain the principal's effectiveness in managing the classroom in elementary schools. The case study method of qualitative research is used in this study. The principals and teachers of the first through sixth grades of the elementary school served as the study's subjects. The study was carried out between August 2021 and April 2022. In this study, questionnaires, interviews, and observational methods were used to collect data. The Miles and Huberman analysis of the data was employed. The study's findings demonstrate how effective the principal is at leading or supervising the teacher's class. Planning, organizing, activating, directing, coordinating, and controlling have all been put into practice by the elementary school's principal.